Microbial community diversity of Jinghong laying hens at peak production based on 16S rRNA sequencing. Issue 1 (1st January 2018) - Fu, Shijun; Guo, Shijin; Wang, Jianjun; Wang, Yumao; Zhang, Zhimei; Shen, Zhiqiang
ABSTRACT: In this study, the diversity within the duodenum (S), jejunum (K) and caecum (M) contents of the three different intestinal gut sections microbiota of 30-week-old (peak production stage) Jinghong laying hens were evaluated. The bacterial DNA was sequentially isolated and the V3 to V4 regions of 16S rRNA genes were amplified. Results showed that the average bacterial sequences from the duodenum, jejunum and caecum content were identified to be 175.33 ± 26.63, 64.00 ± 20.95 and 305.33 ± 4.16 OTUs, respectively. The inherent OTUs were found among duodenum (75), jejunum (2) and caecum (172). The caecum had the highest diversity (Shannon = 5.57 ± 0.06) among the three communities. Firmicutes (65.54%) and Proteobacteria (32.68%) were the predominant bacterial phyla in the duodenum content. Firmicutes (97.27%) was the most commonly detected phyla in the jejunum content. As to the caecum, the relatively prominent phyla were Bacteroidetes and Firmicutes and Fusobacteria, accounting for 48.70%, 28.91% and 15.93%, respectively. At the genus level, Lactobacillus, Helicobacter, Bacillus, Peptoclostridium and Campylobacter were the relatively abundant genera in the duodenum content, accounting for 51.76%, 28.07%, 5.89%, 5.04% and 1.70%, respectively. Within the jejunum content, Lactobacillus was the most commonly detected genera, which represent 96.26% of the total genera.